?HETEROSIS STUDIES ON QUALITY TRAITS IN INTRASPECIFIC CROSSES OF GOSSYPIUM HIRSUTUM L. (Biological Sciences - PJSIR, 1994)
Heterosis was studied in 12 intrahirsuturn hybrids for six quality characters. Heterotic response varied from 1.1 - 26.1 %, 2.00 -32.1 %,0.28 -10.5%,0.9 -3.6%, 9.1 -14.1% and 0.6 -2.3% [or seed index, lint index, ginning outtum, staple length, fibre fineness and fibre strength, respectively. Likewise positive heterobeltiosis ranging from 1.1 -20.7%, 1.9 -21.2%,0.3 -9.1%,0.7 -2.1 %, 8.1 -11.11% and 1% respectively was also observed from the above characters.